An interconnect thin film structure containing an ultra-thin diffusion barrier of tantalum nitride, a method of making and use thereof
Patent Information
- Application Number
- CN202611067271.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]现有技术中,关于TaN作为扩散阻挡层的研究多集中在较厚的TaN膜(>20 nm)或采用溅射法制备,对于超薄TaN(≤10 nm)在ALD-Co体系中的界面阻挡效果以及与后续快速热处理的协同作用缺乏系统研究
[0021]1、阻挡性能:通过对比0 nm、5nm、10 nm TaN界面层发现,当TaN厚度为0 nm时,高温热处理后Co与Si会发生严重互扩散,形成高电阻率硅化物。插入TaN阻挡层后,金属扩散被有效抑,且随着TaN厚度增加(10 nm)时,扩散阻挡效果进一步增强,界面清晰完整。
Smart Images

Figure CN122879673A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of microelectronic functional thin film materials technology, specifically to an interconnect thin film structure containing an ultrathin tantalum nitride diffusion barrier layer, its preparation method, and its application. Background Technology
[0002] Atomic layer deposition (ALD) technology is widely used in the fabrication of high-precision metal thin films (such as Co, Ru, and Pt) and nitride thin films (such as TiN, TaN, and AlN) due to its excellent three-dimensional conformal properties, sub-nanometer thickness control, and low deposition temperature. As integrated circuit feature sizes continue to shrink, traditional copper interconnects face increasingly severe challenges in terms of electromigration resistance and resistivity size effects. Cobalt (Co) thin films are widely regarded as strong candidates for next-generation integrated circuit interconnect materials due to their low resistivity, excellent electromigration resistance, and the feasibility of direct electroplating without a seed layer. Furthermore, cobalt-based thin films also have important applications in ferromagnetic electrodes in magnetic random access memory (MRAM) and magnetic layers in micro / nano inductors, and their performance directly determines the reliability and integration density of devices.
[0003] However, in practical devices, Co thin films typically need to be deposited directly or indirectly on silicon substrates. Co and Si readily interdiffusion under high-temperature processes (such as back-end annealing and rapid thermal annealing), forming high-resistivity cobalt silicide phases (CoSi, CoSi2, etc.), leading to a sharp increase in device resistance, magnetic degradation, and even failure. Therefore, a diffusion barrier layer is often introduced between Co and Si, among which tantalum nitride (TaN) has attracted considerable attention due to its excellent thermal stability, high density, and mature ALD process.
[0004] In existing technologies, research on TaN as a diffusion barrier layer has largely focused on thicker TaN films (>20 nm) or sputtering methods. Systematic studies on the interfacial barrier effect of ultrathin TaN (≤10 nm) in ALD-Co systems and its synergistic effect with subsequent rapid thermal processing are lacking. Furthermore, traditional Co thin film preparation methods (such as evaporation and sputtering) typically result in columnar crystal structures with numerous grain boundaries. At high temperatures, Co atoms readily diffuse along these grain boundaries, making it difficult to completely prevent diffusion even with a TaN interfacial layer. In contrast, ALD-prepared Co thin films exhibit higher density, fewer grain boundaries, and lower impurity content, but their high-temperature stability and compatibility with ultrathin TaN interfacial layers have not been fully explored. Simultaneously, performance comparisons of different interconnecting metal materials (such as Co and Cu) within the same ultrathin TaN barrier layer system are rarely reported.
[0005] Therefore, developing an interconnect thin film structure that can simultaneously utilize the intrinsic advantages of ALD metal thin films (especially cobalt) and the barrier capabilities of ultrathin TaN interfaces, and further improving its performance through optimized rapid thermal processing, has significant application value.
[0006] In view of the above-mentioned defects, the inventors of this invention have finally obtained this invention after a long period of research and practice. Summary of the Invention
[0007] The purpose of this invention is to solve the problem of how to develop an interconnect thin film structure that can simultaneously utilize the intrinsic advantages of ALD metal thin films and the barrier capabilities of ultrathin TaN interfaces, and further improve its performance through optimized rapid thermal processing. In particular, it provides an interconnect thin film structure containing an ultrathin tantalum nitride diffusion barrier layer with cobalt as the preferred interconnect metal, its preparation method, and its application.
[0008] To achieve the above objectives, the present invention discloses an interconnect thin film structure containing an ultrathin tantalum nitride diffusion barrier layer, comprising a substrate, a diffusion barrier layer, and an interconnect metal layer, wherein the diffusion barrier layer is disposed on the substrate, the interconnect metal layer is disposed on the diffusion barrier layer, the thickness of the diffusion barrier layer is less than 10 nm, and the thickness of the interconnect metal layer is less than 100 nm.
[0009] The substrate is a silicon substrate.
[0010] The material of the diffusion barrier layer is selected from any one or more combinations of tantalum nitride, titanium nitride, tungsten nitride, tantalum, aluminum nitride, and tungsten carbide.
[0011] The material of the interconnecting metal layer is any one or more combinations of copper, cobalt, ruthenium, tungsten, and aluminum.
[0012] The diffusion barrier layer is made of tantalum nitride, and the interconnect metal layer is made of cobalt.
[0013] This invention also discloses a method for preparing the above-mentioned interconnect thin film structure containing an ultrathin tantalum nitride diffusion barrier layer, comprising the following steps:
[0014] S1, a diffusion barrier layer is deposited on the substrate using atomic layer deposition technology;
[0015] S2, deposit an interconnect metal layer on the diffusion barrier layer in step S1 to obtain a stacked structure;
[0016] S3, the stacked structure obtained in step S2 is placed in a rapid heat treatment device, and after heat treatment, an inert gas is introduced for cooling to obtain an interconnect thin film structure containing an ultrathin tantalum nitride diffusion barrier layer.
[0017] In step S1, the deposition temperature is 250~350 ℃, and the thickness of the diffusion barrier layer is less than 10 nm.
[0018] In step S2, the deposition temperature is 200~300 ℃, and the thickness of the interconnect metal layer is less than 100 nm.
[0019] In step S3, a vacuum is drawn until the pressure is ≤10 before heating and heat preservation. -3 Pa, heated to 100~700℃ at a heating rate of 100~150 ℃ / s, and held at that temperature for no more than 200 s.
[0020] Compared with existing technologies, the advantages of this invention are as follows: By employing the ALD process to prepare interconnect metal layers (especially cobalt) and introducing a TaN diffusion barrier layer of a specific thickness, combined with precise heat treatment control, the stability and electrical performance of the interconnect structure are significantly improved. Specific advantages are as follows:
[0021] 1. Barrier Performance: By comparing 0 nm, 5 nm, and 10 nm TaN interface layers, it was found that when the TaN thickness is 0 nm, Co and Si undergo severe interdiffusion after high-temperature heat treatment, forming high-resistivity silicides. After inserting a TaN barrier layer, metal diffusion is effectively suppressed, and the diffusion barrier effect is further enhanced with the increase of TaN thickness (10 nm), resulting in a clear and complete interface.
[0022] 2. Excellent thermal stability and high-temperature resistance: The Co / TaN(10nm) / Si multilayer structure prepared by this invention exhibits extremely high thermal stability. After high-temperature heat treatment above 700 °C, the structure still maintains a distinct interface, and no silicide phase formation was detected.
[0023] 3. Synergistic Optimization of Heat Treatment: By performing gradient heat treatment within the range of 100~700 ℃, this invention achieves precise control over the grain size and crystal orientation of Co thin films. After high-temperature heat treatment, ALD-Co / TaN / Si exhibits a Co(111) preferred orientation, which helps to reduce electron scattering. When the TaN thickness is 0 nm, the resistivity of ALD-Co / Si reaches its lowest point after heat treatment at 400 ℃, with a minimum sheet resistance of 3.82 Ω / □. When the TaN thickness is 10 nm, ALD-Co / TaN / Si reaches its lowest point after heat treatment at 700 ℃, with a minimum sheet resistance of 2.51 Ω / □, significantly reducing the parasitic resistance of the interconnects.
[0024] 4. Compared to Co films prepared by vapor deposition, the Co films prepared by the ALD process in this invention exhibit superior thermal and interfacial stability under the same heat treatment conditions. Experiments show that the vapor-deposited Co / Si structure undergoes significant silanization at 500 °C; while the ALD-Co / Si structure maintains a stable Co metal phase at 600 °C, with only slight silanization signs appearing at 700 °C. These results indicate that the ALD process effectively delays the silanization initiation temperature. The Co films prepared by this process have a denser and more uniform microstructure, effectively slowing down Co / Si interfacial interdiffusion and silanization reactions, providing a good structural foundation for further improving interfacial stability and interconnect reliability by combining an ultrathin TaN barrier layer.
[0025] 5. Compared to copper interconnect materials, this invention, through systematic comparative verification, reveals that cobalt metal exhibits superior interface stability and electrical properties under the same TaN diffusion barrier layer and heat treatment conditions, further highlighting the application potential of cobalt as a next-generation interconnect material. The aforementioned intrinsically dense ALD-Co structure and the highly efficient barrier capability of the ultrathin TaN diffusion barrier layer synergistically achieve high-temperature interconnect stability that is difficult to attain through single technical means.
[0026] 6. Process compatibility: All processes adopt ALD and rapid thermal processing, which is compatible with modern semiconductor processes and can be processed in batches. Attached Figure Description
[0027] Figure 1 Schematic diagrams of thin film samples prepared by different processes, where (a) is ALD-Co / TaN(0 / 5 / 10 nm) / Si, (b) is vapor-deposited-Co / TaN(0 / 5 / 10 nm) / Si, and (c) is vapor-deposited-Cu / TaN(0 / 5 / 10 nm) / Si;
[0028] Figure 2 The images show the XRD results of the ALD-Co / TaN(0 nm) / Si composite thin film prepared in Example 1 after heat treatment at different temperatures.
[0029] Figure 3 SEM images of the ALD-Co / TaN(0 nm) / Si composite film prepared in Example 1 after annealing at different temperatures from 100 to 700 °C, where (a) to (h) correspond to the surface morphology at room temperature and at each annealing temperature, respectively.
[0030] Figure 4 The images show the TEM results of the ALD-Co / TaN(0 nm) / Si composite thin film prepared in Example 1 after heat treatment at different temperatures. In the images, (a) is the overall morphology, (bc) is the high-resolution image, (d) is the line scan image, and (e) is the area scan image.
[0031] Figure 5 The images show the XRD results of the ALD-Co / TaN(5 nm) / Si composite thin film prepared in Example 2 after heat treatment at different temperatures.
[0032] Figure 6 SEM images of the ALD-Co / TaN(5 nm) / Si composite film prepared in Example 2 after annealing at different temperatures from 100 to 700 °C, where (a) to (h) correspond to the surface morphology at room temperature and at each annealing temperature, respectively.
[0033] Figure 7 The images show the XRD results of the ALD-Co / TaN(10 nm) / Si composite thin film prepared in Example 3 after heat treatment at different temperatures.
[0034] Figure 8 SEM images of the ALD-Co / TaN(10 nm) / Si composite film prepared in Example 3 after annealing at different temperatures from 100 to 700 °C, where (a) to (h) correspond to the surface morphology at room temperature and at each annealing temperature, respectively.
[0035] Figure 9 The images show the TEM results of the ALD-Co / TaN (10 nm) / Si composite thin film prepared in Example 3 after heat treatment at different temperatures. In the images, (a) is the overall morphology, (b) is the high-resolution image, (cd) is the FFT image, (e) is the line scan image, and (f) is the area scan image.
[0036] Figure 10 XRD results of the vapor-deposited Co / TaN(0 nm) / Si composite thin film prepared in Comparative Example 1 after heat treatment at different temperatures;
[0037] Figure 11 SEM images of the vapor-deposited Co / TaN(0 nm) / Si composite film prepared in Comparative Example 1 after annealing at different temperatures from 100 to 700 °C, where (a) to (h) correspond to the surface morphology at room temperature and at each annealing temperature, respectively.
[0038] Figure 12 The TEM results of the vapor-deposited Co / TaN (0 nm) / Si composite thin film prepared in Comparative Example 1 at different heat treatment temperatures are shown in the figures. (a) is the overall morphology, (b) is the high-resolution image, (cd) is the FFT image, (e) is the line scan image, and (f) is the area scan image.
[0039] Figure 13 XRD results of the vapor-deposited Co / TaN (10 nm) / Si composite thin film prepared in Comparative Example 2 after heat treatment at different temperatures;
[0040] Figure 14 SEM images of the vapor-deposited Co / TaN (10 nm) / Si composite film prepared in Comparative Example 2 after annealing at different temperatures from 100 to 700 °C, where (a) to (h) correspond to the surface morphology at room temperature and at each annealing temperature, respectively.
[0041] Figure 15 The TEM results of the vapor-deposited Co / TaN (10 nm) / Si composite thin film prepared in Comparative Example 2 at different heat treatment temperatures are shown in the figures. (a) shows the overall morphology, (bc) shows the high-resolution images, (d) shows the line scan images, and (e) shows the area scan images.
[0042] Figure 16 XRD results of the vapor-deposited Cu / TaN(0 nm) / Si composite thin film prepared in Comparative Example 3 after heat treatment at different temperatures;
[0043] Figure 17 SEM images of the vapor-deposited Cu / TaN(0 nm) / Si composite film prepared in Comparative Example 3 after annealing at different temperatures from 100 to 600 °C, where (a) to (g) correspond to the surface morphology at room temperature and at each annealing temperature, respectively.
[0044] Figure 18 The TEM results of the vapor-deposited Cu / TaN(0 nm) / Si composite thin film prepared in Comparative Example 3 at different heat treatment temperatures are shown in the figure. (a) is the overall morphology, (b) is the high-resolution image, (cf) is the FFT image, and (g) is the line scan image.
[0045] Figure 19 XRD results of the vapor-deposited Cu / TaN (10 nm) / Si composite thin film prepared in Comparative Example 4 after heat treatment at different temperatures;
[0046] Figure 20 SEM images of the vapor-deposited Cu / TaN (10 nm) / Si composite film prepared in Comparative Example 4 after annealing at different temperatures from 100 to 600 °C, where (a) to (g) correspond to the surface morphology at room temperature and at each annealing temperature, respectively.
[0047] Figure 21 The images shown are TEM results of the vapor-deposited Cu / TaN (10 nm) / Si composite thin film prepared in Comparative Example 4, with different heat treatment temperatures. (a) shows the overall morphology, (bc) shows the high-resolution images, (d) shows the line scan images, and (e) shows the area scan images. Detailed Implementation
[0048] The above-mentioned and other technical features and advantages of the present invention will be described in more detail below with reference to the accompanying drawings.
[0049] Example 1
[0050] ALD-TaN = 0 nm + ALD-Co, heat treatment 100-700 ℃:
[0051] 60 nm Co was deposited on a silicon substrate via ALD: CpCo(CO)2 was used as the precursor, H2 plasma was used as the co-reactant, the deposition temperature was 240 °C, and the number of cycles was approximately 550. The sample was then subjected to rapid thermal annealing at different temperatures in a nitrogen atmosphere for 120 s.
[0052] A schematic diagram of the thin film sample structure is shown below. Figure 1 As shown, Figure 2 XRD analysis showed that for the ALD-Co / Si sample, only characteristic diffraction peaks of Co were detected after annealing at 100–600 °C, and no diffraction signals of any cobalt-silicon compounds (such as CoSi or CoSi2) were detected. After further heating to 700 °C, except for a residual weak Co(111) peak, the remaining Co peaks disappeared, and a CoSi(210) peak appeared, confirming that Co had reacted with Si to form the CoSi phase, but the transformation was not complete.
[0053] Figure 3 SEM showed that for the Co / Si sample, the film remained continuous and flat within the temperature range of 100-400 °C, without significant changes. When the temperature rose to 500 °C, the film exhibited obvious discontinuities, forming island-like structures. Further heating to 700 °C resulted in a significant change in surface morphology, with the appearance of coarse, high-brightness particles. GIXRD analysis confirmed that these particles were silicide phases generated by the Co-Si reaction, indicating that intense interfacial interdiffusion and chemical reactions occurred between the Co and Si substrates at high temperatures.
[0054] Figure 4 TEM analysis of the Co / Si sample after annealing at 700 °C revealed severe thermal agglomeration of the previously continuous Co film, along with significant interdiffusion and interfacial reactions between the Co and Si substrates. High-resolution TEM images and FFT analysis clearly identified the CoSi (210) crystal plane (interface spacing 0.25 nm), confirming the formation of cobalt-silicon compounds at the interface. EDS line and surface scans showed that Co had extensively penetrated into the Si substrate, with significant overlap between Co and Si signals at the interface. These results strongly suggest that a vigorous silanization reaction occurred at the Co / Si interface at 700 °C in the absence of a diffusion barrier layer.
[0055] Example 2
[0056] ALD-TaN = 5 nm + ALD-Co, heat treatment at 100-700 ℃:
[0057] 5 nm TaN was deposited on a silicon substrate by ALD: TBTDET and NH3 plasma were used as precursor and co-reactant, respectively, at a deposition temperature of 275 °C for approximately 40 cycles. Subsequently, 60 nm Co was deposited by ALD (under the same conditions as in Example 1), and the sample was subjected to rapid heat treatment at different temperatures in a nitrogen atmosphere for 120 s.
[0058] A schematic diagram of the thin film sample structure is shown below. Figure 1 As shown, Figure 5 XRD analysis showed that no diffraction signals of any cobalt silicon compounds (such as CoSi or CoSi2) were detected in the sample with a 5 nm TaN barrier layer throughout the entire heat treatment temperature range, indicating that the 5 nm TaN layer effectively suppressed the Co / Si interface reaction.
[0059] Figure 6 SEM images showed that after annealing at 500 °C, obvious particle aggregation and voids appeared on the film surface, and the film changed from a continuous state to an irregular island-like morphology.
[0060] Example 3
[0061] ALD-TaN = 10 nm + ALD-Co, heat treatment at 100-700 ℃:
[0062] A 10 nm TaN layer was deposited on a silicon substrate by ALD (under the same conditions as in Example 2), with approximately 80 cycles. Subsequently, a 60 nm Co layer was deposited by ALD (under the same conditions as in Example 1). The sample was then subjected to rapid thermal annealing at different temperatures in a nitrogen atmosphere for 120 s.
[0063] A schematic diagram of the thin film sample structure is shown below. Figure 1 As shown, Figure 7 XRD showed that for samples with a 10 nm TaN barrier layer, only metallic Co diffraction peaks were present after annealing at 100-700 °C, and no cobalt-silicon compound phase was detected, indicating that the 10 nm TaN layer can effectively suppress the interdiffusion of Co / Si interface at high temperature.
[0064] Figure 8 SEM images showed that the thin film samples exhibited obvious island-like aggregation after annealing at temperatures of 500 °C and above. Figure 9 TEM showed that for the sample with 10 nm TaN deposited, thermal agglomeration occurred on the surface of the Co film after annealing at 700 °C, but the TaN layer remained intact and the interface was clear. Combined with the EDS results, it was found that 10 nm TaN effectively blocked the interdiffusion reaction of Co-Si.
[0065] Comparative Example 1
[0066] To compare the effects of different deposition methods on the thermal stability of thin films, this comparative example uses electron beam evaporation to prepare Co thin films.
[0067] ALD-TaN=0 nm + Co vapor deposition, heat treatment 100-700 ℃:
[0068] A 60 nm Co layer was deposited on a silicon substrate using an evaporation deposition technique. The sample was then subjected to rapid thermal annealing at different temperatures under a nitrogen atmosphere for 120 s.
[0069] A schematic diagram of the thin film sample structure is shown below. Figure 1 As shown, Figure 10 XRD showed that for the vapor-deposited Co / Si sample without a barrier layer, the diffraction peak of metallic Co completely disappeared after annealing at 500 °C, and CoSi diffraction peak appeared. At 600 °C, CoSi2 diffraction peak appeared further, and at 700 °C, it completely transformed into CoSi2. Compared with ALD-Co / Si (Co peaks still remained at 700 °C), the siliconization reaction of vapor-deposited Co was more intense, indicating that ALD-Co has better thermal stability.
[0070] Figure 11 SEM showed that the film surface exhibited good smoothness and flatness at room temperature and after annealing at 100-400 °C. At 500 °C, the film surface cracked and became discontinuous. As the temperature further increased to 600 °C and 700 °C, the aggregation of the film became more intense, and the continuous Co film was completely broken down and transformed into a discontinuous large-sized island structure.
[0071] Figure 12 TEM showed that for the vapor-deposited Co / Si sample without a TaN barrier layer, after annealing at 500 °C, a continuous and thick interfacial reaction layer was formed. The CoSi phase was confirmed by measuring the lattice fringe spacing and combining it with FFT transformation analysis, indicating that Co and the Si substrate had undergone a large-scale silanization reaction.
[0072] Comparative Example 2
[0073] ALD-TaN=10 nm + Co vapor deposition, heat treatment 100-700 ℃:
[0074] 10 nm TaN was deposited on a silicon substrate by ALD (under the same conditions as in Example 2), with approximately 80 cycles. Subsequently, 60 nm Co was deposited by evaporation deposition. The sample was then subjected to rapid thermal annealing at different temperatures in a nitrogen atmosphere for 120 s.
[0075] A schematic diagram of the thin film sample structure is shown below. Figure 1 As shown, Figure 13XRD showed that for vapor-deposited Co / Si samples with a 10 nm TaN barrier layer, only metallic Co diffraction peaks were present in the GIXRD patterns after annealing at 100-700 °C, and no silicide phase was detected, indicating that the 10 nm TaN layer can effectively block the diffusion of Co atoms at high temperatures.
[0076] Figure 14 SEM showed that after heat treatment at 100-700 ℃, the film surface remained smooth and continuous, with only a slight increase in grain size and no cracking or island agglomeration.
[0077] Figure 15 TEM results showed that after annealing at 500 °C, the cross-sectional results showed that the Co / TaN and TaN / Si interfaces were clear and flat, and no reaction layer or signs of interdiffusion were observed.
[0078] Comparative Example 3
[0079] To compare the thermal stability of Co and Cu thin films under the same deposition method, this comparative example uses electron beam evaporation to prepare Cu thin films.
[0080] ALD-TaN=0 nm + Cu vapor deposition, heat treatment 100-600 ℃:
[0081] A 60 nm Cu layer was deposited on a silicon substrate using an evaporation deposition technique. The sample was then subjected to rapid thermal annealing at different temperatures under a nitrogen atmosphere for 120 s.
[0082] A schematic diagram of the thin film sample structure is shown below. Figure 1 As shown, Figure 16 XRD analysis showed that the Cu peak completely disappeared and a Cu3Si peak appeared in the vapor-deposited Cu / Si sample after annealing at 200 °C, indicating that Cu was completely silanized; the Cu3Si peak intensity increased after 500 °C. Compared with the vapor-deposited Co / Si system (CoSi is formed at 500 °C, and CoSi2 is fully formed at 700 °C), the silanization initiation temperature of Cu is about 300 °C lower, indicating that its thermal diffusivity is stronger.
[0083] Figure 17 SEM showed that the surface of the vapor-deposited Cu / Si sample cracked and became very rough and discontinuous after annealing at 200 °C. At 300-600 °C, it completely lost its continuity and agglomerated into discrete island-like particles. Combined with XRD, it can be seen that Cu3Si has been formed at this time.
[0084] Figure 18TEM showed that after annealing at 600 °C, the vapor-deposited Cu / Si sample formed island-like precipitates embedded in the Si substrate at the interface. HRTEM and FFT analysis confirmed that they were Cu3Si phases. EDS showed that the Cu:Si atomic ratio was close to 3:1, indicating that Cu had penetrated and reacted with Si, and the interface structure was severely damaged.
[0085] Comparative Example 4
[0086] ALD-TaN=10 nm + Cu vapor deposition, heat treatment 100-600 ℃:
[0087] 10 nm TaN was deposited on a silicon substrate by ALD (under the same conditions as in Example 2), with approximately 80 cycles. Subsequently, 60 nm Cu was deposited by evaporation deposition. The sample was then subjected to rapid heat treatment at different temperatures in a nitrogen atmosphere for 120 s.
[0088] A schematic diagram of the thin film sample structure is shown below. Figure 1 As shown, Figure 19 XRD analysis showed that after annealing at 100–600 °C, the vapor-deposited Cu / TaN (10 nm) / Si sample only showed Cu and TaN diffraction peaks in the XRD pattern, and no Cu3Si phase appeared, indicating that the 10 nm TaN barrier layer has excellent diffusion blocking performance at high temperatures.
[0089] Figure 20 SEM showed that the surface of the vapor-deposited Cu / TaN (10 nm) / Si sample remained intact after annealing at 100–300 °C; pyramidal Cu particles appeared at 400 °C, and only surface cracking occurred at 600 °C, without significant agglomeration or dehydration. Combined with XRD results, it was confirmed that the TaN layer could effectively block Cu diffusion.
[0090] Figure 21 TEM analysis of the vapor-deposited Cu / TaN (10 nm) / Si sample, after annealing at 600 °C, revealed clear and smooth Cu / TaN and TaN / Si interfaces. HRTEM and FFT detected only Cu crystal plane diffraction features, with no silicide phases observed. EDS line and surface scanning showed steep concentration gradients of Cu and Si elements on both sides of the TaN layer, with no signs of interdiffusion, indicating that the 10 nm TaN layer effectively blocked the interfacial reaction between Cu and Si at 600 °C.
[0091] The above description is merely a preferred embodiment of the present invention and is illustrative rather than restrictive. Those skilled in the art will understand that many changes, modifications, and even equivalents can be made within the spirit and scope defined by the claims of the present invention, all of which will fall within the protection scope of the present invention.
Claims
1. An interconnect thin film structure containing an ultrathin tantalum nitride diffusion barrier layer, characterized in that, It includes a substrate, a diffusion barrier layer, and an interconnect metal layer. The diffusion barrier layer is disposed on the substrate, and the interconnect metal layer is disposed on the diffusion barrier layer. The thickness of the diffusion barrier layer is less than 10 nm, and the thickness of the interconnect metal layer is less than 100 nm.
2. The interconnect thin film structure containing an ultrathin tantalum nitride diffusion barrier layer as described in claim 1, characterized in that, The substrate is a silicon substrate.
3. The interconnect thin film structure containing an ultrathin tantalum nitride diffusion barrier layer as described in claim 1, characterized in that, The material of the diffusion barrier layer is selected from any one or more combinations of tantalum nitride, titanium nitride, tungsten nitride, tantalum, titanium, aluminum nitride, and tungsten carbide.
4. The interconnect thin film structure containing an ultrathin tantalum nitride diffusion barrier layer as described in claim 1, characterized in that, The material of the interconnecting metal layer is any one or more combinations of copper, cobalt, ruthenium, tungsten, and aluminum.
5. The interconnect thin film structure containing an ultrathin tantalum nitride diffusion barrier layer as described in claim 1, characterized in that, The diffusion barrier layer is made of tantalum nitride, and the interconnect metal layer is made of cobalt.
6. A method for preparing an interconnect thin film structure containing an ultrathin tantalum nitride diffusion barrier layer as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S1, a diffusion barrier layer is deposited on the substrate using atomic layer deposition technology; S2, deposit an interconnect metal layer on the diffusion barrier layer in step S1 to obtain a stacked structure; S3, the stacked structure obtained in step S2 is placed in a rapid heat treatment device, and after heat treatment, an inert gas is introduced for cooling to obtain an interconnect thin film structure containing an ultrathin tantalum nitride diffusion barrier layer.
7. The method for preparing an interconnect thin film structure containing an ultrathin tantalum nitride diffusion barrier layer as described in claim 6, characterized in that, In step S1, the deposition temperature is 250~350 ℃, and the thickness of the diffusion barrier layer is less than 10 nm.
8. The method for preparing an interconnect thin film structure containing an ultrathin tantalum nitride diffusion barrier layer as described in claim 6, characterized in that, In step S2, the deposition temperature is 200~300 ℃, and the thickness of the interconnect metal layer is less than 100 nm.
9. The method for preparing an interconnect thin film structure containing an ultrathin tantalum nitride diffusion barrier layer as described in claim 6, characterized in that, In step S3, a vacuum is drawn until the pressure is ≤10 before heating and heat preservation. -3 Pa, heated to 100~700 ℃ at a heating rate of 100~150 ℃ / s, and held at that temperature for no more than 200 s.
10. The application of an interconnect thin film structure containing an ultrathin tantalum nitride diffusion barrier layer as described in any one of claims 1 to 5 in microelectronic interconnects, magnetic storage devices, microelectromechanical systems, or electromagnetic shielding films.